Role of Information Technology Capability and Knowledge Management in Increasing Organizational Agility to Encourage Product Innovation in Semarang - Putri, Naila Diva; Hidayat, Yusmar Ardhi; Budi Utaminingtyas, Rara Ririn (JOBS (Jurnal Of Business Studies), 2024)
This study aims to analyze the effect of information technology capabilities on organizational agility, knowledge management on organizational agility, information technology capabilities on product innovation, knowledge management on product innovation, organizational agility on product innovation. The research variables extend the academic discussion by finding inconsistencies in information technology capabilities and knowledge management on product innovation. Organizational agility is used as a mediating variable. This study is theoretically useful regarding the role of organizational agility as a mediator and managerially used as a foundation for the Semarang Cooperative & MSME Agency in educating the importance of technology and knowledge management, as well as training umkm actors to respond quickly to change. Partial Least Square Structural Equation Model (PLS-SEM) as an analytical tool with primary data obtained through questionnaires. The sample was taken by purposive random sampling from 123 culinary MSME owners in Semarang City who use digital platforms. This study found that information technology capability has a positive effect on organizational agility, knowledge management has a positive effect on organizational agility, and organizational agility has a positive effect on product innovation. However, the relationship between information technology capabilities and knowledge management is not significant to product innovation, and emphasizes the importance of organizational agility as a mediator. The research implication shows that organizational agility optimizes the use of information technology and knowledge management, so that both can contribute significantly to product innovation.